European Society of Cardiology (ESC) clinical consensus statement on indications for conduction system pacing, with special contribution of the European Heart Rhythm Association of the ESC and endorsed by the Asia Pacific Heart Rhythm Society, the Canadian Heart Rhythm Society, the Heart Rhythm Society, and the Latin American Heart Rhythm Society - Glikson, Michael; Burri, Haran; Abdin, Amr; Cano, Oscar; Curila, Karol; De Pooter, Jan; Diaz, Juan C; Drossart, Inga; Huang, Weijian; Israel, Carsten W; Jastrzębski, Marek; Joza, Jacqueline; et al. (Europace, 2025)
Conduction system pacing (CSP) is being increasingly adopted as a more physiological alternative to right ventricular and biventricular pacing. Since the 2021 European Society of Cardiology pacing guidelines, there has been growing evidence that this therapy is safe and effective. Furthermore, left bundle branch area pacing was not covered in these guidelines due to limited evidence at that time. This Clinical Consensus Statement provides advice on indications for CSP, taking into account the significant evolution in this domain.
Keywords: převodní systém srdeční; Europe; Indications; Biventricular pacing; výsledek terapie; Action Potentials; lidé; Evropa; konsensus; Treatment Outcome; Left bundle branch area pacing; Arrhythmias, Cardiac; společnosti lékařské; Cardiac resynchronization therapy; Cardiac Pacing, Artificial; Societies, Medical; srdeční frekvence; Consensus; His bundle pacing; kardiologie; Cardiology; Heart Conduction System; kardiostimulace umělá; Conduction system pacing; Heart Rate; srdeční arytmie; akční potenciály; Humans